2022
DOI: 10.3390/cells11203271
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Role of Pyroptosis in Myocardial Ischemia-Reperfusion Injury

Abstract: Myocardial ischemia-reperfusion injury (MIRI) results in the aggravation of myocardial injury caused by rapid recanalization of the ischemic myocardium. In the past few years, there is a growing interest in investigating the complex pathophysiological mechanism of MIRI for the identification of effective targets and drugs to alleviate MIRI. Currently, pyroptosis, a type of inflammatory programmed death, has received greater attention. It is involved in the MIRI development in combination with other mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 123 publications
0
15
0
Order By: Relevance
“…28 The aforementioned nine programs participate in complex mechanisms underlying the death of cardiomyocytes. 29,30 Among these, ferroptosis is considered a contributor to I/R injury;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 The aforementioned nine programs participate in complex mechanisms underlying the death of cardiomyocytes. 29,30 Among these, ferroptosis is considered a contributor to I/R injury;…”
Section: Discussionmentioning
confidence: 99%
“…These cell death programs, particularly the regulated forms of cardiomyocyte death, play significant roles in major cardiac syndromes such as MI with reperfusion and heart failure 28 . The aforementioned nine programs participate in complex mechanisms underlying the death of cardiomyocytes 29,30 . Among these, ferroptosis is considered a contributor to I/R injury; hence, targeting ferroptosis may be a promising protective therapy against I/R injury 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The nature of MIRI in Chinese medicine mainly lies in two aspects of root vacuity and tip repletion, which interact with each other and jointly affect the pathological process of MIRI. Among them, root vacuity refers to a deficiency of qi and insufficient blood circulation and Yin and Yang, while tip repletion refers to phlegm turbidity, cold coagulation, qi stagnation, blood stasis, and other phenomena ( Li et al, 2021 ). The TCM pathogenesis of MIRI includes qi deficiency, blood stasis, and phlegm turbidity.…”
Section: Research Progress On the Mechanisms Of Mirimentioning
confidence: 99%
“…Studies have confirmed that most flavonoids have a certain protective effect on the myocardium, and the bioactive components of Huangqin elicit a cardiac protective effect through some channels ( Sun W. et al, 2021 ). Li and Yu’s (2021) study has shown that WG could increase Nrf2 expression and regulate the redox system balance in MIRI rats ( Li et al, 2021 ). Additionally, the expression of HO-1 also increased.…”
Section: Herb Medicines and Their Active Chemical Ingredients In Tcm ...mentioning
confidence: 99%
“…Treating cerebral ischemia is particularly challenging because of the rapid progression of the injury 3 . Inflammatory reactions initiated at the blood–microvessel interface a few hours after the onset of ischemia underlie the transition from ischemic to inflammatory injury 4 . A phenomenon called ischemia–reperfusion injury is often observed once blood flow is restored.…”
Section: Introductionmentioning
confidence: 99%